The Lyrical Cycle of A.A. Blok “Italian Poems”: Poetic Reception of Italy and the Culmination of the Period of “Antithesis” - Tatjana A. Koshemchuk; Marina S. Samarina (Studia Litterarum)
The lyrical cycle of the A.A. Block “Italian Poems” (1909) is a travelogue of the poet (a number of contemplated cities), it is considered from three points of view: as reflecting the isolation of the poet-lyricist on his own experiences and embodying the central theme of Blok, denoted as passion; as a unity of variations in the composition of the whole (not previously considered), in the development of the poet’s central theme; as the part of the third volume in the concept of the poet’s path, which in spirit is the culmination of the period of “antithesis.” The Italian theme is analyzed in variations of the poet’s dominant intention, in the cycle it is the search for the object of passion. First, the history of Italy as a story of extinct passions awakening the passions of the poet (Galla); then the real women of Italy; finally, the poet’s passion turns to the Madonna of frescoes and sculptures, giving rise to demonic motives and blasphemously erotic culminations. The development of the theme of passions (realhistorical, feminine and Eternally Feminine) leads to the assertion of immortal art in the transitory world. The analysis of Blok’s Italian cycle suggests introducing of the new accents into the concept of the poet’s path, of its three stages: the cycle marks not the harmonization and search for synthesis of the third volume, but a dark culmination in the spirit of the period of tragic substitutions and “falls” of the “antithesis” stage.